Photoconductivity of MEH-PPV/TiO2 nanocomposite thin films / Fazlinashatul Suhaidah Zahid - Zahid, Fazlinashatul Suhaidah (2010)
This paper investigates the photoconductivity of the MEH-PPV/TiO2 nanocomposite thin films by varying the weight ratio of TiO2 and was deposited on the glass substrates by using spin coating technique. The influence of the amount of TiO2 in the nanocomposite heterojunctions and photoconductivity as prepared blends compared to the single component of MEH-PPV was characterized by using Voltage/Current (I-V) measurement in dark and under illumination, UV-VIS spectrophotometer and Field Emission Scanning Electron Microscopy (FESEM). For electrical properties measurements in dark and under illumination show that, the resistivity decreases and conductivity increases when the amount of TiO2 increases. While for optical properties measurements shows the optical band gap increases when the amount of TiO2 increases. The surface morphology images also shows that the MEH-PPV/TiO2 particles uniformly shaped but there are some large clusters were observed between the surface nanostructures.